Perception of men who collaborate in a higher education institution on your health care (Research, Society and Development, 2021)
In an attempt to enrich health education content, the challenges faced by men in relation to their health needs were observed. The recognition of facilitating and expanding the access of the male population to health services is an initiative that results from the observation that male injuries are considered a public health problem. In order to reflect the perception of male collaborators at a Brazilian university about their health care. This is a qualitative, descriptive and exploratory study, through a focus group based on communication and interaction, with a group of 06 people and approximately 70 minutes of collection, with the purpose of addressing nursing in men's health, the data were analyzed through content analysis. However, care that is often not seen as a male culture, men need the practice of health policies that aim to promote and prevent more active primary care. It is worth mentioning that the creation of the National Policy for Integral Attention to Men's Health, as a major step towards acting in men's health, has not yet noticed effective changes in the Unified Health System, but it looks forward to a promising future in the area.